High energy pulsed fiber lasers - Zhang, Meng (2018)
Short-pulse fiber lasers have found a variety of applications covering micromachining, medical imaging, ophthalmology, precision metrology, etc. Particularly, it is widely used for material processing in industrial applications. With the rapid development brought by Industry 4.0, huge performance improvements are also required from pulsed fiber lasers. With the aim of improving the performance of high energy pulsed fiber lasers, we have researched eight important aspects. Firstly, in order to have a good overview of the best existing fiber laser technologies, literatures have been reviewed thoroughly. Secondly, in order to master laser-matter interactions, we proposed and explored a novel material processing technique using a high energy femtosecond pulsed laser. Thirdly, with an in-depth understanding of the laser technologies and applications, we began to build our own fiber laser starting with investigating the backbones of fiber lasers, rare-earth-doped fibers. We analyzed its key feature, the absorption and emission of electromagnetic radiation, and reported a problem commonly encountered in conventional absorption spectrum measurement for the first time in the world. New approaches have also been proposed and evaluated. Fourthly, in order to make a breakthrough in the power limits of pulsed fiber lasers, we have analyzed various physical power limiting factors and have found the prospective solutions. Fifthly, we have designed and constructed our first picosecond fiber laser system, which is a compact, fully fiberized system with tunable pulse-width, high pulse repetition rate and a high peak power of ~100 kW for material processing in industry. Sixthly, in order to get pulse energy higher than through conventional short pulses, we created abnormal noise-like pulses through a mode-locking fiber laser system. Seventhly, in order to increase the versatility of fiber lasers in various applications, we have built a second Yb-doped picosecond pulse fiber laser system with pulse shaping capability. Pulse shaping has been accomplished in the temporal and spatial domains (in donut modes) simultaneously, generating different pulse shapes at an average output power > 10 W. Lastly, in order to improve the transmission of infrared laser in donut modes, we designed and optimized a novel fiber for broadband low-loss infrared laser transmission (in both fundamental modes and donut modes). This fiber design is also practical to fabricate. Overall, this thesis makes novel contributions to the field from several different aspects. It proposes new material processing technique facilitating advanced devices fabrication. It also points out significant errors in the conceptually simple but very important absorption measurement related to all active fiber devices. Moreover, it covers the construction of three pulsed fiber laser systems with tunable pulse-width and high peak power, abnormal noise-like pulses, and simultaneous arbitrarily temporal shaping and spatial mode shaping, respectively. Additionally, it introduces a practical novel fiber design for infrared transmission in different modes. The technique, the measurement, the three fiber laser systems and the fiber design can all benefit not only research in the lab but also applications in the industries.